Economic Status of the Tourism Sector during the COVID 19 Pandemic at Lake Toba Parapat - Raisha Ghadati Raudina; Anthoni Veery Mardianta (Talenta Publisher, 2022)
Parapat is the main gateway to Samosir Island and is often referred to as Parapat Tourism City. The presence of Lake Toba with its natural beauty makes the surrounding area a priority object and tourist attraction (ODTW) in North Sumatra. Currently, the Lake Toba area is designated as the National Tourist Destination (DPU) in North Sumatra. At the beginning of 2020, the world was shaken by the presence of the Covid-19 virus outbreak. The Indonesian government has also acted to contain the spread of Covid-19 by implementing the policy